Indonesia's VAT Rate Increase and Its Implications for Purchasing Power and Economic Growth: A Critical Review - Huda Trihatmoko; Salsabila Rahmadini (Journal of Sharia Economics, Banking and Accounting, 2026)
This study critically examines the implications of Indonesia's Value Added Tax (VAT) rate increase for fiscal sustainability, purchasing power, and economic growth through a Critical Literature Review (CLR) approach. Previous studies have largely examined these issues separately, resulting in fragmented evidence regarding the broader economic consequences of VAT policy. This study synthesizes and critically evaluates academic literature, government reports, regulations, and publications from international organizations to develop a more comprehensive understanding of the multidimensional effects of VAT reforms. The findings indicate that VAT rate increases contribute positively to government revenue and fiscal sustainability but may simultaneously generate inflationary pressures and reduce household purchasing power, particularly among low-income groups. The review further demonstrates that the overall impact on economic growth depends on the government's ability to allocate additional tax revenue efficiently through productive public expenditure and appropriate social protection measures. By integrating fiscal sustainability, purchasing power, public welfare, and economic growth into a single analytical framework, this study contributes to a more balanced understanding of VAT policy and provides policy implications for designing equitable and sustainable fiscal reforms in Indonesia.